CSF dynamic analysis of a predictive pulsatility-based infusion test for normal pressure hydrocephalus. - Qvarlander, Sara; Malm, Jan; Eklund, Anders (Medical & Biological Engineering & Computing, 2014)
Disturbed cerebrospinal fluid (CSF) dynamics are part of the pathophysiology of normal pressure hydrocephalus (NPH) and can be modified and treated with shunt surgery. This study investigated the contribution of established CSF dynamic parameters to AMP(mean), a prognostic variable defined as mean amplitude of cardiac-related intracranial pressure pulsations during 10 min of lumbar constant infusion, with the aim of clarifying the physiological interpretation of the variable. AMP(mean) and CSF dynamic parameters were determined from infusion tests performed on 18 patients with suspected NPH. Using a mathematical model of CSF dynamics, an expression for AMP(mean) was derived and the influence of the different parameters was assessed. There was high correlation between modelled and measured AMP(mean) (r = 0.98, p < 0.01). Outflow resistance and three parameters relating to compliance were identified from the model. Correlation analysis of patient data confirmed the effect of the parameters on AMP(mean) (Spearman's ρ = 0.58-0.88, p < 0.05). Simulated variations of ±1 standard deviation (SD) of the parameters resulted in AMP(mean) changes of 0.6-2.9 SD, with the elastance coefficient showing the strongest influence. Parameters relating to compliance showed the largest contribution to AMP(mean), which supports the importance of the compliance aspect of CSF dynamics for the understanding of the pathophysiology of NPH.